A common genetic variation in GZMB may associate with cancer risk in patients with Lynch syndrome - Grolmusz, Vince Kornél; Nagy, Petra; Likó, István; Butz, Henriett; Pócza, Tímea; Bozsik, Anikó; Papp, János; Oláh, Edit; Patócs, Attila (Frontiers in Oncology, 2023)
Lynch syndrome (LS), also known as hereditary nonpolyposis colorectal cancer syndrome (HNPCC) is a common genetic predisposition to cancer due to germline mutations in genes affecting DNA mismatch repair. Due to mismatch repair deficiency, developing tumors are characterized by microsatellite instability (MSI-H), high frequency of expressed neoantigens and good clinical response to immune checkpoint inhibitors. Granzyme B (GrB) is the most abundant serine protease in the granules of cytotoxic T-cells and natural killer cells, mediating anti-tumor immunity. However, recent results confirm a diverse range of physiological functions of GrB including that in extracellular matrix remodelling, inflammation and fibrosis. In the present study, our aim was to investigate whether a frequent genetic variation of GZMB, the gene encoding GrB, constituted by three missense single nucleotide polymorphisms (rs2236338, rs11539752 and rs8192917) has any association with cancer risk in individuals with LS. In silico analysis and genotype calls from whole exome sequencing data in the Hungarian population confirmed that these SNPs are closely linked. Genotyping results of rs8192917 on a cohort of 145 individuals with LS demonstrated an association of the CC genotype with lower cancer risk. In silico prediction proposed likely GrB cleavage sites in a high proportion of shared neontigens in MSI-H tumors. Our results propose the CC genotype of rs8192917 as a potential disease-modifying genetic factor in LS.